The Implementation of Muthlaq and Muqayyad Rules in the Determination of Family Maintenance: A Methodological Analysis of the Nash-nash of Islamic Family Law - Erniawati; Nur Taufiq Sanusi; Fatmawati; Mohamad Subli (PT. Nawa Edukasi Nusantara, 2026)
This research analyzes the implementation of muthlaq and muqayyad principles in determining family maintenance (nafkah) through a methodological approach to Islamic family law texts. The study addresses the complexity of interpreting absolute (muthlaq) and conditional (muqayyad) legal texts in contemporary family maintenance determination. Using qualitative library research with textual analysis (tahlil an-nushush), comparative analysis (al-manhaj al-muqaran), and contextual analysis methods, this research examines primary sources including the Quran, hadith collections, and classical fiqh literature. The findings reveal that Quranic verses and prophetic traditions combine muthlaq and muqayyad expressions, providing flexibility while establishing boundaries in maintenance standards. Different Islamic schools (madhabs) apply these principles with varying approaches: Hanafi emphasizes contextual flexibility, Shafi'i focuses on standardization of basic needs, while Hanbali prioritizes balance between rights and obligations. The implementation in Indonesian family law, particularly through the Compilation of Islamic Law (KHI) and religious court decisions, demonstrates the relevance of classical ushul fiqh methodology for addressing contemporary family law issues. This research contributes a theoretical framework for analyzing contemporary family law matters using muthlaq-muqayyad principles.